Cell-penetrating Peptide-mediated Nanovaccine Delivery - Jiang, Jizong (Current Drug Targets, 2021)
Vaccination with small antigens, such as proteins, peptides, or nucleic acids, is used to activate the immune system and trigger the protective immune responses against a pathogen. Currently, nanovaccines are undergoing development instead of conventional vaccines. The size of nanovaccines is in the range of 10-500 nm, which enables them to be readily taken up by cells and exhibit improved safety profiles. However, low-level immune responses, as the removal of redundant pathogens, trigger counter-effective activation of the immune system invalidly and present a challenging obstacle to antigen recognition and its uptake via antigen-presenting cells (APCs). In addition, toxicity can be substantial. To overcome these problems, a variety of cell-penetrating peptide (CPP)-mediated vaccine delivery systems based on nanotechnology have been proposed, most of which are designed to improve the stability of antigens in vivo and their delivery into immune cells. CPPs are particularly attractive components of antigen delivery. Thus, the unique translocation property of CPPs ensures that they remain an attractive carrier with the capacity to deliver cargo in an efficient manner for the application of drugs, gene transfer, protein, and DNA/RNA vaccination delivery. CPP-mediated nanovaccines can enhance antigen uptake, processing, and presentation by APCs, which are the fundamental steps in initiating an immune response. This review describes the different types of CPP-based nanovaccines delivery strategies.
Keywords: vaccine